Basic study of intrinsic elastography: Relationship between tissue stiffness and propagation velocity of deformation induced by pulsatile flow. (17th June 2015) - Nagaoka, Ryo; Iwasaki, Ryosuke; Arakawa, Mototaka; Kobayashi, Kazuto; Yoshizawa, Shin; Umemura, Shin-ichiro; Saijo, Yoshifumi
Abstract: We proposed an estimation method for a tissue stiffness from deformations induced by arterial pulsation, and named this proposed method intrinsic elastography (IE). In IE, assuming that the velocity of the deformation propagation in tissues is closely related to the stiffness, the propagation velocity (PV) was estimated by spatial compound ultrasound imaging with a high temporal resolution of 1 ms. However, the relationship between tissue stiffness and PV has not been revealed yet. In this study, the PV of the deformation induced by the pulsatile pump was measured by IE in three different poly(vinyl alcohol) (PVA) phantoms of different stiffnesses. The measured PV was compared with the shear wave velocity (SWV) measured by shear wave imaging (SWI). The measured PV has trends similar to the measured SWV. These results obtained by IE in a healthy male show the possibility that the mechanical properties of living tissues could be evaluated by IE.